2017
DOI: 10.1038/s41598-017-02102-7
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent conductance in Sb2SeTe2 topological insulator nanosheets

Abstract: The conductivity increases as thickness decreases in a series of Sb2SeTe2 topological insulator nanosheets with thickness ranging from 80 to 200 nm, where the sheet conductance is proportional to the thickness. The corresponding sheet conductance of the surface state is 8.7 e2/h which is consistent with the values extracted from the temperature dependent Shubnikov-de Haas oscillations at high magnetic fields. The extracted Fermi momentum is the same as the results from the ARPES value, and the Berry phase is π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The resultant material was then used as a feeding rod for the RHFZ experiment. Our previous work demonstrated that TI with extremely high uniformity can be obtained using the RHFZ method 8 , 9 , 21 23 . After growth, the crystals were furnace cooled to room temperature.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The resultant material was then used as a feeding rod for the RHFZ experiment. Our previous work demonstrated that TI with extremely high uniformity can be obtained using the RHFZ method 8 , 9 , 21 23 . After growth, the crystals were furnace cooled to room temperature.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Several experimental works were performed on different topological insulators, which exhibited various kinds of characteristics that are expected to be able to be used in a wide range of applications. [10][11][12][13][14][15][16][17][18] It has come to our attention that most photocurrent experiments have mainly focused on the application of visible and near infrared light to topological insulators, graphene-topological insulator heterostructures and 2D TMDs. Work with ultraviolet light is relatively rare, and the reported photocurrent performance is low.…”
Section: Introductionmentioning
confidence: 99%
“…1 , the linear voltage-current relation supports that nanosheets reveal a metallic behavior. The light-induced electron-hole pairs would travel to two electrode contacts due to the applied voltage bias [ 27 29 ]. Following Ohm’s law, the related photocurrent could be determined through the relation I ph = V G where V is the applied voltage bias between two electrodes.…”
Section: Resultsmentioning
confidence: 99%